Statin therapy and outcomes in trials of nintedanib in idiopathic pulmonary fibrosis - Kreuter, Michael; Costabel, Ulrich; Richeldi, Luca; Cottin, Vincent; Wijsenbeek, Marlies; Bonella, Francesco; Bendstrup, Elisabeth; Maher, Toby M.; Wachtlin, Daniel; Stowasser, Susanne; Kolb, Martin (Respiration, 2018)
Background: Cardiovascular comorbidities are frequent in patients with idiopathic pulmonary fibrosis (IPF), and many patients with IPF receive treatment with statins to reduce cardiovascular risk. Objectives: We investigated whether statin use at baseline was associated with differences in disease progression in placebo-treated patients or influenced the treatment effect of nintedanib in the INPULSIS® trials. Methods: Post-hoc subgroup analyses of patients receiving versus not receiving statins at baseline using pooled data from the INPULSIS® trials. Results: At baseline, 312 patients received statins and 749 did not. The annual rates of decline in forced vital capacity (FVC) in patients treated with nintedanib and placebo, respectively, were -78.9 and -187.6 mL/year in patients who received statins at baseline, and -127.9 and -237.9 mL/year in patients who did not. The effect of nintedanib was consistent across subgroups (p = 0.9590). Conclusions: In the INPULSIS® trials, there was a numerically lower FVC decline in placebo-treated patients with IPF who received statins at baseline versus those who did not. Use of statins at baseline did not influence the treatment effect of nintedanib. Prospective data are needed to assess the impact of statins on the course of IPF.
Gesehen am 29.10.2019